Effects of Genetic Polymorphisms of Glutathione S-transferase P1 on Helicobacter pylori-associated Gastric Cancer (Gut and Liver, 2008)
Background/Aims: Glutathione S-transferase P1 (GSTP1) scavenges radicals via its peroxidase activity. The purpose of this study was to determine the association of GSTP1 genetic polymorphisms with the expression of H. pylori-associated gastroduodenal disease. Methods: This study involved 1,911 subjects, comprising patients with four diseases (gastric cancer, dysplasia, benign gastric ulcer, and duodenal ulcer disease) and controls. Biallelic polymorphisms were genotyped by restriction fragment length polymorphism techniques. Results: The frequency of the genetic polymorphism at nucleotide 313 of GSTP1 did not differ among the five study groups. However, when the gastric cancer group was subdivided into advanced gastric cancer (AGC) and early gastric cancer, the frequency of the G/G genotype was significantly higher in the AGC group than in all the control subgroups (OR: 1.2, 95% CI: 1.1-4.9). The frequency of this genotype differed significantly in the H. pylori-positive AGC group (OR: 2.7, 95% CI: 1.1-6.3) but not in the H. pylori-negative group. Furthermore, the difference was greater in the intestinal type, and was not found in diffuse types of disease. Conclusions: This study found that genetic polymorphisms of GSTP1 were associated with H. pylori-associated gastric cancer only during the advanced stage of gastric cancer, with intestinal-type histology evident in H. pylori-positive subjects. (Gut and Liver 2008;2:23-29)